KARAKTER KUALITATIF DAN HUBUNGAN KEKERABATAN BEBERAPA GENOTIPE CABAI (Capsicum annuum L.) (The Qualitative Characterization and The Genetic Relationship of Chillies Genotypes (Capsicum annuum L.)) - Anis Tatik Mariyani (Bioplantae, 2012)
The research purposed to find out the agronomic characteristics of 10 chillies genotypes and relationship between genotypes. The experiments was conducted at Experiment Plantation at Leuwikopo, Bogor Agricultural University, Darmaga, from March to August 2011. The research showed that there is a significant differences between genotypes in the qualitative character. The genetic relationship of all genotypes tested and the qualitative character looks at the form of rods, the number of flowers by axil, the crown form of flowers, the colors of ripes fruits, the beginning of fruits form and the tip form of fruits.Keywords : Chillies, characterization, qualitative